Oral Health Status and Treatment Needs of Elderly in Phitsanulok - Samnieng, Patcharaphol (Asian Health, Science and Technology Reports, 2016)
Oral health is an important part of overall wellbeing of elderly in Thailand. Studies in many countries show that oral health status of elderly is poor and there is an urgent need to improve. Assessment of the oral health status and the needs of older people will aid in the organization of a prevention-oriented oral health care program to improve the quality of life of elderly. The purpose of this study was to describe the oral health status and dental treatment needs of an elderly population. The subjects were elderly people (60-92 years old), who live in Phitsanulok, Thailand. A total of 612 participants (158 males and 454 females, mean age 68.8±5.9) agreed to join the study. The oral examination was performed by one dentist to detect periodontal status The Community Periodontal Index: (CPI) and dental caries status ware reported as decayed, missing, or filled teeth (DMFT), followed those recommendation by the World Health Organization. In addition, prosthetic status and treatment needs were classified according to WHO criteria and also recorded. Information on self-perceived oral health problems, oral function and oral health behavior was obtained via questionnaires. The results showed that, thirty percent of subjects had no natural teeth. The mean DMFT score was 18.9±8.3 (DT=2.0±2.8, MT=16.3±8.3, FT=0.7±2.2) teeth per person. The mean number of DMFT and MT significantly increased with age, with MT dominating in the DMFT index (p<0.05). Thirty-five percent of subjects needed dental fillings and 20 % required tooth extractions. The percentage of elderly with shallow (4-6mm) and deep (>6 mm) periodontal pockets were 9.6 and 26.6 respectively. Half (49.9%) of all subject needed periodontal treatment. Forty-eight percent of subjects need both upper and lower jaw partial dentures, 8.5 % needed complete dentures. The top five of self-perceived oral problems of elderly were: dental caries; gum disease; halitosis; difficulty in chewing hard food and tooth sensitivity. The oral health status of elderly examined in this study was poor due to high levels of tooth loss, caries experience and prevalence of periodontal pockets. Dental care, especially prosthetic care, should be focused upon. Thus, oral health program that emphasizes prevention should be considered of particular important for elderly.